New species of the genus Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from Guangxi, South China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2012)
Six species of the genus Lathrobium Gravenhorst, 1802 from Guangxi, South China are described: L. dayaoshanense sp. n., L.maoershanense sp. n., L. proprium sp. n., L. shengtangshanense sp. n., L. zhangdinghengi sp. n. and L. zhujianqingi sp. n. Illustrations of major diagnostic features and a key to the species from Guangxi are provided.